The Clinical Success of Inlay-Retained Fixed Partial Dentures - (:unkn) unknown (AVES PRESS LTD, 2016)
Implant-supported crowns, traditional full-coverage fixed dental prostheses, removable prostheses, and inlay-retained fixed partial prostheses are treatment options for the rehabilitation of a single missing tooth. With the increasing importance of the conservative approach in dentistry, minimal invasive preparation for optimal restorations is becoming popular. When implant treatment option is refused by young individuals with extensive pulp, surgical procedures are contraindicated and there is a risk for a pulp exposure during the preparation of the abutment teeth, therefore inlay-retained restorations are indicated. In these cases, inlay-retained fixed prostheses are more conservative than conventional bridges. This review aims to evaluate the long-term clinical success of inlay-retained fixed prostheses.
Keywords: Inlay-retained prostheses; metal-ceramic; all-ceramic; fiber reinforced composite